POR UMA PEDAGOGIA DECOLONIAL E LIBERTÁRIA - Massadar Morel, Ana Paula; Latini Pfeil, Cello; Xavier de Santana, Guilherme (Revista Estudos Libertários, 2023)
Editorial - Por uma pedagogia decolonial e libertária!